Analyses the Performance of Data Warehouse Architecture Types - Jameel, Karwan; Adil, Abdulmajeed; Bahjat, Maiwan (Journal of Soft Computing and Data Mining, 2022)
The concept of storing historical data for retrieving them when needed has been conceived, and the idea was primitive to build repositories for historical data to store these data, despite the use of a specific technique for recovering these data from various storage modes. Data warehouse is the most reliable and widely used technology for scheduling, forecasting, and managing corporations, also concern with the data storage facility that extensive collection of data. Data warehouses are called ancient modern techniques; since the early days of relational databases, the critical component of decision support, increasing focus for the database industry. Many commercial products and services are now available, and almost all of the primary database management system vendors provide them. When opposed to conventional online transaction processing applications, decision support puts slightly different demands on database technology. This paper analyzes the performance of the data warehouse architectures, through studding and comparing many research works in this filed. the study involves the extract, transform and load the data from deferent recourses and the imporatnt charactrestic of the architectures types, Furthermore the tools and application service techniques used to build data warehouse architecture.